To B12 or not to B12: Five questions on the role of cobalamin in host-microbial interactions - Rowley, Carol A.; Kendall, Melissa M. (PLoS pathogens, 2019)
Ruminants are heavily colonized with cobalamin-producing microbes in the rumen, a specialized organ that allows fermentation of ingested feed, and this cobalamin is later absorbed in the small intestine [3]. [...]unlike most mammals, cattle are able to use the cobalamin produced by bacteria that colonize their own gastrointestinal tract without the practice of coprophagy. In support of the latter idea, during in vitro growth, members of the genus Bacteroides that are common intestinal bacteria outcompete IF for binding to cobalamin [5], suggesting that bacteria interfere with absorption in vivo. [...]broad-spectrum tetracycline antibiotic therapy resolves cobalamin deficiency in human subjects [6]. Only 25% of bacteria in the gastrointestinal (GI) tract synthesize cobalamin, whereas 80% of bacteria encode cobalamin-dependent enzymes [7]. [...]bacteria rely heavily on cobalamin-uptake mechanisms to acquire sufficient levels from the surrounding environment. AdoCbl is not a true cofactor because this molecule undergoes irreversible Co-C bond cleavage during EA catabolism, and each round requires a new or readenoslyated AdoCbl molecule for enzyme activity. [...]besides encoding metabolic genes, the eut operons of the Firmicutes and Enterobacteriaceae also carry distinct regulatory elements that require cobalamin to drive eut expression.